Petrophysical zoning elements of Chertovo Koryto gold-ore deposit (Patom Upland, Eastern Siberia); IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Sokolov S. V. Stepan Vitalievich (Geophysical Surveying Methods for Ore Deposit Prospecting. Geoinformation Systems in Geophysical Surveys, 2015)
Title screen